Fungal Infection in Cystic Fibrosis - Sarvestani, Amirmehdi; Almasian, Mohammad; Nafari, Amirhossein (Current Respiratory Medicine Reviews, 2021)
Background: The prevalence of fungal infections has been increasing in recent years. Cystic fibrosis (CF) is a genetic disorder that affects organs such as the intestines, liver, pancreas, and especially the lungs. Introduction: Fungal pathogens are becoming a challenge in CF. Advanced medical science is associated with longer life expectancy in some patient groups. Method: A review was conducted on studies found on online databases, including Google Scholar, PubMed, and Scopus. Internet-based searches were performed on these databases for cystic fibrosis, respiratory infections, and fungal infection profiling to identify all relevant studies published between 2010 and 2020. Result: Fungal pathogens most frequently isolated from the respiratory tract include the Aspergillus genus, the Candida genus, Scedosporium apiospermum, and the Rasamsonia genus. In cystic fibrosis, these organisms usually colonize the respiratory and intestinal tracts and cause hypersensitivity responses and invasive diseases. Conclusion: Fungus-patient interactions are complicated and depend on various factors. Moreover, the emergence of drug-resistant species is a serious health issue, and the development of new treatments is crucial.
Keywords: airway colonization